2020
DOI: 10.7307/ptt.v32i4.3399
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Effects of Land Use on the Choice of Intra-Zonal Trip Destinations – A Comparison Between Weekday and Weekend Travel

Abstract: Among the studies on the land use – travel relationship, few investigated it regarding weekend travel and destination choice. This study accordingly evaluates how the land use - destination choice relationship differs between weekdays and weekends using two multinomial logistic regression models in which the destination is classified into three types: microzone inside, microzone outside - macrozone inside, and macrozone outside. Major findings are that the choice of automobile alternatives for travel and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Seoul citizens were more likely to choose cars for weekend travels. It seemed to be related to the importance of punctuality for commute travels during weekdays (Bhat & Srinvasan, 2005; Gim, 2020). The trip duration tended to affect the perception of trips and influences the travel mode choice (Humagain & Singleton, 2021; Ye et al, 2020); however, in this study, the effects of trip duration was not observed because of expressed travel utility that may affect travel satisfaction was controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seoul citizens were more likely to choose cars for weekend travels. It seemed to be related to the importance of punctuality for commute travels during weekdays (Bhat & Srinvasan, 2005; Gim, 2020). The trip duration tended to affect the perception of trips and influences the travel mode choice (Humagain & Singleton, 2021; Ye et al, 2020); however, in this study, the effects of trip duration was not observed because of expressed travel utility that may affect travel satisfaction was controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies regard trip characteristics (e.g., Gim, 2020; Humagain & Singleton, 2021; Milakis et al, 2015), socio‐economic characteristics (e.g., Ferrer et al, 2018; Ha et al, 2020; Limtanakool et al, 2006), and built environment (e.g., Handy et al, 2002; Khan et al, 2014; Ye & Titheridge, 2017) as control variables to investigate the relationship between travel utility and travel mode choice. Although these variables constitute different hierarchical levels and different scales, most studies consider them as the same hierarchical level and analyze them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Hanoi, Vietnam, Nguyen et al [31] used a logit model for destination choice and an ordered probit model for trip generation with socio-demographic, mobility and accessibility and built environment factors. Gim [32] used multinomial logistic regression models to analyze the relationship between land use and destination choice separately for weekday and weekend travel with land use variables, trip characteristics and individual and household socio-demographics. However, these studies focused on personal trips and trip purpose, which could not be addressed in this study.…”
Section: Introductionmentioning
confidence: 99%